2013
DOI: 10.3390/en6042191
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Evaluation of Tidal Stream Energy and the Impacts of Energy Extraction on Hydrodynamics in the Taiwan Strait

Abstract: Tidal stream speeds in straits are accelerated because of geographic and bathymetric features. For instance, narrow channels and shallows can cause high tidal stream energy. In this study, water level and tidal current were simulated using a three-dimensional semi-implicit Eulerian-Lagrangian finite-element model to investigate the complex tidal characteristics in the Taiwan Strait and to determine potential locations for harnessing tidal stream energy. The model was driven by nine tidal components (M 2 , S 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…[2] assessed the effects of TCP extraction on water level for an estuarine area, they concluded that both the decrease in the maximum water level and the increase in the minimum are kept below 0.05 m. Chen et al [38] estimated the influences of TCP extraction on water level for the Taiwan Strait using the momentum sink approach. Their study results found that TCP extraction at a specific farm could significantly affect the tidal current, but the change in tidal amplitude and tidal phase could be neglected.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] assessed the effects of TCP extraction on water level for an estuarine area, they concluded that both the decrease in the maximum water level and the increase in the minimum are kept below 0.05 m. Chen et al [38] estimated the influences of TCP extraction on water level for the Taiwan Strait using the momentum sink approach. Their study results found that TCP extraction at a specific farm could significantly affect the tidal current, but the change in tidal amplitude and tidal phase could be neglected.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…The wetting and drying scheme is naturally incorporated into the model for inundation studies. Due to their highly flexible frameworks, the SELFE and SCHISM models have been widely used to solve cross-scale problems: general circulation [29], storm surges [30], tsunami hazards [31], water quality [32], oil spills [33], sediment transport [34,35], biogeochemistry [36,37], and assessment of tidal stream energy resources [9,38]. A two-dimensional version of SCHISM, SCHISM-2D, is employed in this study since Kinmen Island is surrounded by shallow coastal waters (as shown in Figure 2a).…”
Section: Hydrodynamic Modelmentioning
confidence: 99%
“…Because of their high scalability, the SCHISM and SELFE modeling systems have been employed to solve water quality and hydrodynamic problems in estuarine and coastal environments in Taiwan. For instance, estuarine residence time, suspended sediment, and fecal coliform transport were simulated (Liu et al, 2008;Chen et al, 2015;Chen and Liu, 2017), storm tide-induced coastal inundation was assessed Liu, 2014, 2016), and tidal current energy was evaluated (Chen et al, 2013(Chen et al, , 2017a.…”
Section: Configuration Of the Schism-wwm-iii Modeling Systemmentioning
confidence: 99%
“…The location of these regions is presented in Figure 2. To obtain the power potential of the Morocco Atlantic coast and the Mediterranean Sea the values were obtained for one square meter cross-sectional area, therefore using the following formula [27]:…”
Section: Steps Descriptionmentioning
confidence: 99%